Mediator analysis job satisfaction: The relationship between work life balance and turnover intentions - Wahid Sumarjo; Dedeh Kurniasih; John Chaidir; Tajudin Tajudin; Surya Alam (Institute of Accounting Research and Novation (IARN), 2026)
This study aims to analyze the effect of work-life balance on turnover intention with job satisfaction as a mediating variable in employees of PT San Fang Indonesia. This study used a quantitative approach with saturated sampling techniques involving 95 respondents. Data were collected through a Likert scale questionnaire and analyzed using the PLS-SEM method with SmartPLS 4. The results of the study show that work-life balance has a negative and significant effect on turnover intention, as well as a positive and significant effect on job satisfaction. Job satisfaction has also been shown to have a significant negative effect on turnover intention. In addition, job satisfaction plays a significant mediator in the relationship between work-life balance and turnover intention. These findings indicate that improving work-life balance not only directly decreases employee exit intentions, but also through increased job satisfaction. This research emphasizes the importance of organizational policies that support work-life balance to increase job satisfaction and reduce turnover rates. The results of this study make an empirical contribution to the development of human resource management strategies, especially in the manufacturing sector.